Managing landfill leachate using biological approach - Er, Xin Yi (2020)
Poor management of landfill would accompany with the production of leachate wastewater that would lead to environmental and public hazards. Hence, a study related to the use of biological treatment for leachate management was carried out.The research objectives of this research study were pathogenic microorganism detection, raw leachate wastewater characterization and identification of effective leachate treatment. A leachate sample was collectedfrom both Simpang Renggam Landfill and Bakri Landfill via compositing sampling method.The leachate sample was collected from two sampling points at the leachate drain. Selective selection and serological test had been carried out and the microorganism detected in the leachate samples were Escherichia coli, Staphylococcussp and Listeriasp.Triplicate samples of each raw leachate wastewater were used for leachate characterization. The parameters used for leachate characterization were chemical oxygen demand measured via Reactor Digestion method and ammonia nitrogen concentration measured via Nesslerization method. Besides that,the heavy metals content in the leachate sample were measured via Atomic Absorption Spectroscopy. The ammonia nitrogen concentration and chemical oxygen demand in the raw leachate samples show that both leachate samples were characterized as mature leachate. Brevibacillus panacihumi strain ZB1 was used for biological treatment and lightweight aggregate was used for adsorption process. Triplicate of each leachate samples were treated via sole biological treatment, combined dilution with biological treatment and combined adsorption with biological treatment. Removals of ammonia nitrogen from both Simpang Renggam and Bakri leachate samples treated by three treatments were nearly37% to 47%, 63% to 77% and 83% while chemical oxygen demands removed were 37% to 42%, 63% to 75% and 41% to 74%, respectively. Although final concentration of pollutants after treatment processes exceeded the discharge standard, all treatment methods proved able to reduce the pollutants concentration.